Online foods order and delivery service: a pilot study - Kedah, Zulkarnain; Yusof, Ismail (2010)
There has been a growing trend among providers of physical products and services to shift from purely „traditional‟ to „online‟ modes of receiving orders online and thereafter affecting deliveries via suitable means. Success factors in traditional business offering may not be wholly applicable for online mode of business. Consequently, there is a need to conceptualize a specific model for inevitable online food ordering and delivery. By synthesizing the literature in related areas, this paper aims to propose important components that explain customer placement of food order online and consequent delivery. Available literature suggests that order placement (OP), a dependent variable is made up of two main components, that is, online food ordering (as first independent variable) and delivery services (second independent variable). The study proposed a model and provided testable hypotheses. It carried out a pilot test to obtain general feelings of prospective online orders from urban dwellers. Fast service and convenience have been cited as main factors to make city dwellers want to place their food order online. Factors that dissuade city people to experience online purchase include unknown service provider, low food quality, type and variety of food and perceived lack of online security protection.